Prevalence of Subclinical Hypothyroidism in Patients with Type II Diabetes Mellitus and Its Impact on Patient’s Lipidemic Status? - Mudhafar Sami Khazaal (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Diabetes mellitus (DM) is a chronic endocrine diseases characterized by raised blood glucose level. Current data predict that the DM prevalence will reach up to 11% of the world`s population in 10 years from now. Subclinical hypothyroidism (SCH) is a condition where the circulating thyroid-stimulating hormone is elevated and free thyroxine and free tri-iodothyronine are within normal. This condition is associated with hypercholesterolemia. Dyslipidemia is a lipid imbalance that can result in complications affecting the cardiovascular system in particular. A common cause of dyslipidemia is diabetes. The correlation between subclinical hypothyroidism and type II DM is controversial. The aim of the study was to investigate the association between SCH and type II DM, and if there is an impact of SCH on diabetic dyslipidemia. Methods. A case-control study conducted from January 2018 to January 2023 in Kerbala, Iraq. It included 176 patients with type II DM and 180 subjects as controls. The study was carried on after the approval of the ethical committee at Kerbala College of medicine. Results. SCH was more prevalent (18.18%) in the diabetic versus (2.22%) in the control groups, (p<0.0001, OR = 9.78, 95% CI [3.38 to 28.29]). Females had higher prevalence of SCH (68.1% vs 45.46%) and (1.67% vs 0.56%) for diabetic and control groups, respectively. Dyslipidemia was more prevalent in the diabetic group (45.46%) versus (8.33%) in control groups, (p<0.0001, OR = 9.17, 95% CI [4.99 to 16.08]). Conclusion. The prevalence of SCH was higher in type II DM and in females. The dyslipidemia was more pronounced in diabetics with SCH. The degree of lipid control correlated with the TSH level, duration of diabetes and the degree of glycemic control.